Current challenges and promising avenues for entrepreneurship research - Rose Mary Almeida Lopes; Edmilson Lima (RAE: Revista de Administração de Empresas, 2019)
The research field of entrepreneurship has shown a significant increase in scientific production in the last two decades (Landström & Harirchi, 2018a), attracting researchers from many disciplines (Zahra, 2007). There has been a considerable increase in the quality of the research and legitimacy of the field (Audretsch, 2012; Davidsson, 2016). However, this research field still faces considerable challenges in its continuous advancement. The field has several different definitions for basic concepts and approaches (Landström & Lohrke, 2010), and still lacks consensus on, for example, what is its object of study (Burg & Romme, 2014; Machado & Borges, 2017). Thus, there are different understandings about what entrepreneurship means – generation of a result (e.g., creation of a new organization), discovery and exploitation of opportunities, and entrepreneurial process or action (Machado & Borges, 2017; Shane & Eckhardt, 2003; Shane & Venkataraman, 2000), among others.